Thermal signature analysis as a novel method for evaluating inflammatory arthritis activity. Issue 3 (8th September 2005) - Brenner, M; Braun, C; Oster, M; Gulko, P S
Abstract : Objective: To examine the potential usefulness of a novel thermal imaging technique to evaluate and monitor inflammatory arthritis activity in small joints using rat models, and to determine whether thermal changes can be used to detect preclinical stages of synovitis. Methods: Three different rat strains were studied in a model of inflammatory arthritis of the ankle induced by an intra-articular (IA) injection of complete Freund's adjuvant (CFA), compared with the contralateral ankle injected with normal saline. Arthritis activity and severity scores, ankle diameters, pain related posture scores, and thermal images were obtained at 10 different times between 0 h (before induction) and day 7. The pristane induced arthritis (PIA) model was used to study preclinical synovitis. Thermal images were obtained at each time point using the TSA ImagIR system and were digitally analysed. Results: Rats developed similar ankle arthritis detected six hours after the IA injection of CFA, which persisted for seven days. All ankle clinical indices, including arthritis activity and severity scores, correlated significantly with ankle thermal imaging changes in the monoarthritis model (p<0.003). No thermal imaging changes were detected in preclinical stages of PIA. However, PIA onset coincided with increased ankle thermal signature. Conclusions: Thermal measurements correlated significantly with arthritis activity and severity indices. The technique was highly sensitive and could measure directly two cardinal signs of inflammation (warmth and oedema, based on ankle diameter) in an area (ankle) that is less than half the size of a human interphalangeal joint, suggesting a potential use in drug trials or clinical practice.